Hemostatic factor levels and cognitive decline in older adults: The Cardiovascular Health Study. (29th March 2021) - Harrington, Laura B.; Ehlert, Alexa N.; Thacker, Evan L.; Jenny, Nancy S.; Lopez, Oscar; Cushman, Mary; Fitzpatrick, Annette; Mukamal, Kenneth J.; Jensen, Majken K.
Abstract: Background: Hemostasis is a key factor in cerebrovascular disease, but the association of hemostatic factors with cognitive decline is unclear. Objective: To prospectively evaluate associations of 20 hemostatic factor levels with changes in cognition during ≥8 years of follow‐up in the Cardiovascular Health Study (CHS) of older adults. Methods: We included participants of an existing CHS cross‐sectional substudy ( n = 400) with hemostatic factors measured in 1989‐1990. Between 1989‐1990 and 1998‐1999, cognitive function was measured using the Modified Mini‐Mental State Examination (3MSE) and Digit Symbol Substitution Tests. Mixed‐effects linear regression models estimated change in cognitive function over time, adjusting for sociodemographic and clinical factors and APOE genotype, using Bonferroni adjustment. We also derived principal components to account for the interrelationship among factors. Results: Of 20 factors evaluated individually, only higher levels of plasmin‐α2 ‐antiplasmin complex (PAP), tissue factor pathway inhibitor (TFPI), and lower factor X (FXc) levels were associated with faster cognitive decline, estimated by annual change in 3MSE points (1 standard deviation PAP β = −0.65, 95% confidence interval [CI]: −1.08 to −0.21; TFPI β = −0.55, 95% CI: −0.90 to −0.19; FXc β = 0.52, 95% CI: 0.21‐0.84). One of four principal components, loading positively on D‐dimer, prothrombin fragment 1.2 (F1.2), and PAP was significantly associated with change in 3MSE. Conclusions: Levels of PAP, TPFI, and FXc and a combination of factors driven by PAP, D‐dimer, and F1.2 were associated with cognitive decline. Whether these findings can be used to improve dementia prevention or prediction requires further study.